Religious Moderation and Nationalism According to NU Scholars - Syafi’i; Sukirman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to analyze the views of the Nahdlatul Ulama (NU) Ulama regarding religious and national moderation. In the context of a pluralistic Indonesia, religious moderation is expected to be a solution to overcome the problems of extremism and intolerance that often arise, while the concept of nationality plays an important role in maintaining harmony between religious communities. To achieve this aim, this research uses qualitative methods with in-depth interview techniques and document analysis. Data was obtained from NU ulama who have experience and deep understanding of moderation and nationality issues, both in local and national contexts. The theory used in this research is the theory of religious pluralism, which emphasizes the importance of mutual respect, recognition of diversity, and interreligious dialogue in building social harmony. The research results show that NU ulama emphasize the need for balance between faith and nationality, as well as an active role in maintaining tolerance in society. They argue that religious moderation is not just an attitude, but must also be realized in real actions that can strengthen solidarity between religious communities. It is hoped that these findings can make a significant contribution to the development of religious moderation strategies in Indonesia, as well as become a reference for public policies that support harmonious national life. By understanding the perspective of NU ulama, it is hoped that better cooperation can be established between various elements of society in creating a tolerant and peaceful environment. This research also suggests the need for educational programs that prioritize moderation and national values ​​for future generations, so that the vision of harmony and unity can continue to be maintained and strengthened.